Revisiting the Question: The Cause of the Solar Cycle Variation of Total Solar Irradiance - N. B. Xiang (Advances in Astronomy)
The Mg II index and sunspot area are usually used to represent the intensification contribution by solar bright structures to total solar irradiance (TSI) and sunspot darkening, respectively. In order to understand the cause of the solar cycle variation of TSI, we use extension of wavelet transform, wavelet coherence (WTC), and partial wavelet coherence (PWC), to revisit this issue. The WTC of TSI with sunspot area shows that the two time series are very coherent on timescales of one solar cycle, but the PWC of TSI with sunspot area, which can find the results of WTC after eliminating the effect of the Mg II index, indicates that the solar cycle variation of TSI is not related to sunspots on the solar surface. The coherence of two time series at these timescales should be due to a particular phase relation between sunspots and TSI. The WTC and PWC of TSI with Mg II index show that the solar cycle variation of TSI is highly related to Mg II index, which reflects the relation of TSI with the long-term part of Mg II index that shows the intensification contribution by the small magnetic features to TSI. Consequently, the solar cycle variation of TSI is dominated by the small magnetic features on the solar full disk. Additionally, we also show the combined effects of the sunspot darkening and the intensification contribution represented by Mg II index to TSI on timescales of a few days to several months and indicate that the faculae increase TSI and contribute to its variation at these timescales.